2017
DOI: 10.3138/cpp.2016-077
|View full text |Cite
|
Sign up to set email alerts
|

Financing Innovation in the Yangtze River Economic Belt: Rationale and Impact on Firm Growth and Foreign Trade

Abstract: Le rô le de plus en plus important que jouent les intermédiaires dans la promotion de l'innovation et de l'internationalisation des entreprises donne lieu à un nombre croissant d'études. La Chine a subi des pressions croissantes pour s'intéresser de plus près aux finances des entreprises et favoriser l'innovation. On sait toutefois peu de choses sur les activités des financiers entrepreneuriaux et leurs performances en Chine. En se basant sur les activités de ces financiers dans la zone économique du delta du … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…(In Chinese). 2 The North-Western region is mostly desert and mountains, and is far from coastal cities, it is located high above the sea level and usually has dry weather, often suffering from the lack of rain. Mineral resources in the north-western part include coal, oil, and gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(In Chinese). 2 The North-Western region is mostly desert and mountains, and is far from coastal cities, it is located high above the sea level and usually has dry weather, often suffering from the lack of rain. Mineral resources in the north-western part include coal, oil, and gas.…”
Section: Resultsmentioning
confidence: 99%
“…It is composed of the Yangtze River Delta, Yangtze River Middle Reaches clusters and the Chengdu-Chongqing cluster. With Jing-Jin-Ji and the PRD, they form the most important locomotive of China's economy (Cheng et al 2017). In mainland China, there are 19 city clusters that have been built or are under planning, and the above five are the most promising.…”
Section: Urbanization and City Clusters In Mainland Chinamentioning
confidence: 99%
“…More scholars for instance Cheng, Y et al(2017) also argued that the increasingly large role of financial intermediaries in promoting firms' innovation and internationalization has led to great research interest. China has faced mounting pressure to take entrepreneurial finance and innovation seriously.…”
Section: 11patterns Of Innovation Growthmentioning
confidence: 99%
“…As one of the important development regions in China, the innovation of the YREB has received the attention and research of many scholars. Cheng, Y et al [34] focused on the activities of entrepreneur financiers in the YREB, and made relevant research on financing innovation activities in the Yangtze River Delta region; Liu Y et al [35] studied the spatial integration of urban agglomeration in the YREB and its relationship with industrial development, so as to provide support for future regional spatial integration and coordinated development; Zou L et al [36] studied the efficiency of high-tech innovation in the region and found that the efficiency of high-tech innovation in China is continuously improving, but the regional differences are large, and put forward policy recommendations on the research conclusions; Meng D et al [37] analyzed the spatial agglomeration effect of listed companies in China's YREB and its causes, and studied the main factors affecting their innovation efficiency. Yi M et al [38] studied the impact of government research and development subsidies and environmental regulations on green innovation efficiency of the manufacturing industry in China's YREB; Li X et al [39] took the Yangtze River Economic Zone as the research object to explore the impact of foreign direct investment on high-quality economic development under environmental regulations.…”
Section: Introductionmentioning
confidence: 99%